Welander distal myopathy is caused by a mutation in the RNA‐binding protein TIA1. Issue 4 (11th February 2013) - Hackman, Peter; Sarparanta, Jaakko; Lehtinen, Sara; Vihola, Anna; Evilä, Anni; Jonson, Per Harald; Luque, Helena; Kere, Juha; Screen, Mark; Chinnery, Patrick F.; Åhlberg, Gabrielle; Edström, Lars; et al.
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to identify the molecular cause of Welander distal myopathy (WDM), a classic autosomal dominant distal myopathy. Methods The genetic linkage was confirmed and defined by microsatellite and single nucleotide polymorphism haplotyping. The whole linked genomic region was sequenced with targeted high‐throughput and Sanger sequencing, and coding transcripts were sequenced on the cDNA level. WDM muscle biopsies were studied by Western blotting and immunofluorescence microscopy. Splicing of TIA1 and its target genes in muscle and myoblast cultures was analyzed by reverse transcriptase polymerase chain reaction. Mutant TIA1 was characterized by cell biological studies on HeLa cells, including quantification of stress granules by high content analysis and fluorescence recovery after photobleaching (FRAP) experiments. Results The linked haplotype at 2p13 was narrowed down to <806 kb. Sequencing by multiple methods revealed only 1 segregating coding mutation, c.1362 G>A (p.E384K) in the RNA‐binding protein TIA1, a key component of stress granules. Immunofluorescence microscopy of WDM biopsies showed a focal increase of TIA1 in atrophic and vacuolated fibers. In HeLa cells, mutant TIA1 constructs caused a mild increase in stress granule abundance compared to wild type, and showed slower average fluorescence recovery in FRAP. Interpretation WDM is caused by mutated TIA1 through a dominant pathomechanism probably involving altered stress granule dynamics. Ann Neurol 2013;73:500–509